Application of The Waterfall Method to the Website-Based JM Leather & Shoes Point of Sales Information System - Ni Wayan Jeri Kusuma Dewi; I Gede Made Yudi Antara; Defri Sucahyono (Universitas Pendidikan Nasional, 2024)
Trading business is a type of business that has the basic concept of buying supplies of goods and reselling them with the aim of making a profit. In the current era, people continue to flock to set up a place of business, this is due to changes in market conditions as well as increasingly sophisticated economy and technology. JM Leather & Shoes continues to supervise and record the processing of goods data, supplier data, expenditure data, sales transactions, purchase transactions, and the preparation of reports which are always evaluated every month by superiors. During this time, both cashiers and administration record in the ledger. This of course causes various problems. Where the process of making reports takes a relatively long time, because the administration must first adjust the real stock at the place of business with the stock in the records until finally the difference between the two is found. One effort that can be made is to create an application that can help facilitate business process activities and minimize the occurrence of errors that could have a negative impact on the company's future. With this system, the data processing process from searching, adding, changing, to creating reports as evaluation material becomes easier and faster. The risk of data loss or damage can also be reduced to a minimum because it has been stored in the database, making it more effective and efficient. Future researchers are expected to add features for forecasting the items that are most and least desired by customers.